Cyclic oxidation of high-silicon spheroidal graphite iron. (November 2021) - Ebel, André; Marsan, Olivier; Lacaze, Jacques; Malard, Benoit
Abstract: In service, automotive exhaust manifolds are submitted to rapid thermal cycling up to 700–750 °C. To simulate an increase in exhaust gas temperature, a high-silicon cast iron was tested for rapid thermal cycling up to 800 °C. In addition to the well-known duplex oxide scale, rapid cyclic oxidation promotes the formation of a columnar zone at the substrate/oxide interface that has never been reported. It is evidenced that this columnar zone proceeds from a repetitive process. Based on detailed metallographic analysis using optical observations, in-situ XRD, micro-analyses and Raman spectroscopy, a mechanism explaining the formation of this columnar zone is proposed. Highlights: The oxidation of a high silicon spheroidal graphite cast iron was studied during 3000 rapid thermal cycles up to 800 °C. The oxidation kinetics could be modeled by a parabolic growth law. A columnar zone at the metal/matrix interface is revealed which gives a layered structure in the oxide scale. A repetitive schematic process is proposed for the formation of this columnar structure.